Bifunctionalised long-wavelength fluorescent probes for biological applications - Firmino, A. D. G. (2012)
The synthesis of benzo[a]phenoxazinium chlorides which are bifunctionalised in position 2 with 4-ethoxy-4-oxobutoxyl, 3-hydroxypropoxyl or 3-chloropropoxyl groups, and in position 9 with the (aminopropyl)amino group, was efficiently performed. The covalent labeling of valine was carried out by using one of the new fluorophores obtained. Photophysical studies in the homogeneous media of ethanol, distilled water and at simulated physiological conditions revealed that all the compounds absorbed and emitted from 610 to 651 nm.